Ex-vivo ureteroscopy of deceased donor kidneys - Machen, Graham L. (Can Urol Assoc J, 2017)
INTRODUCTION: When encountered, the ideal management of lithiasis in deceased donor kidneys is not well-defined. With advances in endourological techniques, minimally invasive treatments are becoming an increasingly viable option. We set out to describe our experience performing ex-vivo ureteroscopy on cadaveric donor kidneys, including one in which the procedure was completed on-pump. METHODS: A retrospective chart review was undertaken to identify patients who had undergone ex-vivo ureteroscopy prior to cadaveric renal transplant. Four patients were identified, including one in which the procedure was done with the kidney remaining on-pump. The surgical technique and subsequent data were reviewed. RESULTS: Ex-vivo ureteroscopy was successfully completed in all four instances without intraoperative complication. All kidneys were endoscopically stone-free. Creatinine nadirs ranged from 0.8–1.4. All four patients remained stone-free at a mean followup of 13 months. CONCLUSIONS: Our series provides further evidence as to the safety and efficacy of ex-vivo ureteroscopy prior to transplantation in cadaveric renal transplants and describes a novel technique in the form of on-pump ex-vivo ureteroscopy.